Passage from India: the life and times of His Divine Grace A. C. Bhaktivedanta Swami Prabhupāda; a summary study - Rosen, Steven (Munshiram Manoharlal Publishers, 1992)
Life and work of A.C. Bhaktivedanta Swami Prabhupada, 1896-1977, founder of the International Society for Krishna Consciousness